How sustainability reporting affects equity capital costs: Sustainability assurance and assurance providers as moderating variables - Hamidah, Hamidah; Naimah, Zahroh (International Journal of Management and Sustainability, 2025)
This research provides empirical evidence on how sustainability reporting is associated with reduced equity capital costs, in particular moderating the role of sustainability assurance and Big Four accounting firms. Drawing from the database of listed companies on the Indonesia Stock Exchange, this research will employ Ordinary Least Square (OLS) regression with robust standard errors in testing the hypotheses. The findings indicate a significant negative relationship between sustainability reporting and the cost of equity capital, with sustainability assurance and Big Four firm involvement amplifying this effect. However, it should be noted that the sample size in this study is quite small, and adoption of the Global Reporting Initiative (GRI) G4 standard has been very recent, so generalizations should not be drawn from this study. The findings indicate that, beyond securing credible assurance, the quality of sustainability reports plays a crucial role in enhancing the credibility of financial reporting. This research is one of the first attempts to examine these relationships within the context of a developing country, Indonesia.